A normative theory of luck - Liu, Chengwei; Tsay, Chia-Jung (Frontiers in Psychology, 2023)
Psychologists have identified heuristics and biases that can cause people to make assumptions about causes and patterns in phenomena that actually result from randomness. Yet interpretation of these biases becomes ambiguous when they represent reasonable cognitive shortcuts that offer certain advantages. This paper addresses this ambiguity by presenting a normative theory of luck that integrates insights from psychology with the chance model approach to predict the circumstances under which performance non-monotonicity occurs: higher performance may not only indicate greater luck, but also lower expected merit. We offer an illustrative application of this theory by examining the decoupling of citations of academic publications and their impact, illuminating when citations can be an unreliable indicator of impact or merit. We discuss the implications of a normative theory of luck, including how to remedy or arbitrage the ways people mistake luck for skill.